Autobiographical progression : Christa Wolf's Nachdenken über Christa T., Kindheitsmuster and Ein Tag im Jahr - Nunan, Anna (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2009)
Christa Wolf's Nachdenken über Christa T., Kindheitsmuster and Ein Tag im Jahr constitute a significant contribution to the field of women's autobiographical writing in their in-depth questioning of autobiographical conventions and their emphasis on the complications for women in writing autobiographically.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin.